Analisis Faktor-Faktor Yang Mempengaruhi Return Saham Dengan Kebijakan Dividen Sebagai Variabel Intervening - Admin, Tedy Sumadi B1021161039 (Jurnal Manajemen Update, 2020)
AbstractThis study aims to determine the effect of liquidity, profitability, solvency, investment opportunities, and size growth on stock return with dividend policy as an intervening variable in companies that consistently enter the Kompas 100 index in the 2013-2017 period. The data analysis technique used is multiple linear regression analysis. The results of this study indicate simultaneously CR, ROA, DER, PER, and SG significantly influence DPR and CR, ROA, DER, PER, SG, and DPR significantly influence RS. Partially by using two regression models give results where only ROA, PER, and SG variables have a significant effect on the DPR in the first model and in the second model, only PER and SG variables have a significant effect on RS. Keywords: Stock return, dividend policy, liquidity, profitability, solvency, investment opportunities, and size growthReferensi Abor, J. & Bokpin, G. A. (2010). Investment Opportunities, Corporate Finance, and Dividend Payout Policy. Journal Economics and Finance Emerald Insight, 27, (3), 180-194.Adrianingtyas, D. A. & Sucipto, A. (2019). Pengaruh Kinerja Keuangan dan Keputusan Investasi Terhadap Nilai Perusahaan Dengan Kebijakan Dividen Sebagai Variabel Intervening. Jurnal Ekonomi dan Pendidikan, 2, (2), 23-30.Ambarwati, Sri Dwi Ari. (2010). Manajemen Keuangan Lanjut. Yogyakarta: Graha IlmuAng, R. (1997). Buku Pintar Pasar Modal Indonesia Edisi Pertama. Jakarta: Rineka Cipta.Astuti, R. A., Ritonga, K., & Azhar, A. (2014). Pengaruh Pertumbuhan Aset, Profitabilitas, dan Pertumbuhan Penjualan Terhadap Struktur Modal Pada Perusahaan Real Estate Dan Properti Yang Terdaftar Di Bursa Efek Indonesia Periode 2010-2012. JOM FEKON. 1, (2), 1-15.Arilaha, Asril. (2009). Pengaruh Free Cash Flow, Profitabilitas, Likuiditas, dan Leverage Terhadap Kebijakan Dividen. Jurnal Keuangan dan Perbankan, 13, (1), 78-87Brigham, E. F. & Houston, J. (2004). Dasar-Dasar Manajemen Keuangan Edisi Kesepuluh (II) Edisi Kesepuluh. Jakarta: Salemba Empat.Brigham, E. F. & Houston J. (2011). Dasar-Dasar Manajemen Keuangan Edisi Kesebelas (II) Edisi Kesebelas. Jakarta: Salemba Empat.Bursa Efek Indonesia.Chasanah, N. & Sucipto, A. (2019). Liquidity Ratio, Profitability, and Solvency On Stock Returns With Capital Structure As An Intervening Variable (Study On Food and Beverage Sub Sector Listed In Indonesia Stock Exchange (IDX) Period 2013-2017. Jurnal Bisnis dan Manajemen, 3, (1), 52-68.Dharmawan, B. & Riza, F. (2019). Pengaruh Investment Opportunity Set Terhadap Nilai Perusahaan Dengan Mediasi Kebijakan Dividen (Studi Empiris Pada Emiten Yang Tergabung Dalam Index LQ45). Business Management Journal, 15, (1), 53-61.Fahmi, I. (2012). Analisis Laporan Keuangan. Bandung: Alfabeta.Fahmi, I. (2013). Analisis Laporan Keuangan. Bandung: Alfabeta.Fahmi, I. (2014). Pengantar Pasar Modal. Bandung: Alfabeta.Fahmi, I. (2014). Pengantar Manajemen Keuangan. Bandung: Alfabeta.Farkhan & Ika. (2013). Pengaruh Rasio Keuangan Terhadap Return Saham Pada Perusahaan Manufaktur di Bursa Efek Indonesia (Studi Kasus Pada Perusahaan Manufaktur Sektor Food and Beverage). Jurnal Value Added, 9, (1), 1-18.Ghozali, I. (2011). Ekonometrika Teori, Konsep, dan Aplikasi Dengan SPSS 17. Semarang: Badan Penerbit Universitas Diponegoro.Gitosudarmo, I. & Basri. (2002). Manajemen Keuangan Edisi Keempat. Yogyakarta: BPFE.Hadi, N. (2013). Pasar Modal: Acuan Teoretis Dan Praktis Investasi Di Instrument Keuangan Pasar Modal. Yogyakarta: Graha Ilmu.Hanafi, M. M. (2015). Manajemen Keuangan Edisi Pertama. Yogyakarta: BPFEHarjito, D. A. & Martono. (2001). Manajemen Keuangan. Jakarta: Fakultas Ekonomi Universitas Islam Indonesia.Harmono. (2009). Manajemen Keuangan. Jakarta: PT Bumi Aksara.Hartono, J. (2009). Teori Portofolio dan Analisis Investasi Edisi Keenam. Yogyakarta: BPFE.Hartono, J. (2017). Teori Portofolio dan Analisis Investasi Edisi Kesebelas. Yogyakarta: BPFE.Jannah, R. & Haridhi, M. (2016). Pengaruh Kebijakan Dividen, Earning Volatility, dan Leverage Terhadap Volatilitas Harga Saham Pada Perusahaan Non-Financing Yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014. Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 1, (1), 133-148.Kallapur, S. & Trombley, M. A. (1999). The Association Between Investment Opportunity Set Proxies and Relized Growth. Journal of Business Finance & Accounting, 26, (3-4), 505-519.Mardiyah, A. A. (2001). Pengaruh Asimetri Informasi dan Disclosure Terhadap Cost of Equity Capital. Jurnal Riset Akuntansi Indonesia, 5, (2), 229-256.Munawir. (2005). Analisis Laporan Keuangan. Yogyakarta: Liberty.Myers, S. C. (1977). Determinant of Corporate Borrowing. Journal of Financial Economics, 5, 147-155.Nalurita. (2015). The Effect Of Profitability Ratio, Solvability Ratio, Market Ratio On Stock Return. Journal Business and Enterpreneurial Review, 15, (1), 73-94.Perwira, A. A. G. A. N. & Wiksuana, I. G. B. (2018). Pengaruh Profitabilitas dan Pertumbuhan Aset Terhadap Kebijakan Dividen dan Nilai Perusahaan. E-Jurnal Manajemen Unud, 7, (7), 3767-3797.Prawiranegara, B. (2015). Pengaruh Investment Opportunity Set Terhadap Return Saham (Suatu Studi Pada Perusahaan Astra International Tbk). Jurnal Wawasan dan Riset Akuntansi, 2, (2), 89-102.Purnami, K. D. A. & Artini, L. G. S. (2016). Pengaruh Investment Opportunity Set, Total Asset Turn Over, dan Sales Growth Terhadap Kebijakan Dividen. E-Jurnal Manajemen Unud, 5, (2), 1309-1337.Priyatno, D. (2014). SPSS 22 Pengolahan Data Terpraktis.Yogyakarta: CV Andi Offset.Riawan. (2017). Pengaruh Kebijakan Dividen Dalam Memediasi Return On Asset dan Firm Size Terhadap Return Saham. Jurnal Akuntansi dan Pajak, 17, (2), 37-48.Sanusi, A. (2014). Metodologi Penelitian Bisnis. Jakarta: Salemba Empat.Sari, K. A. N., & Sudjarni, L. K. (2015). Pengaruh Likuiditas, Leverage, Pertumbuhan Perusahaan, dan Profitabilitas Terhadap Kebijakan Dividen Pada Perusahaan Manufaktur di BEI. E-Jurnal Manajemen Unud, 4, (10), 3346-3374.Sartono, A. (2014). Manajemen Keuangan Teori dan Aplikasi Edisi Keempat. Yogyakarta: BPFE.Sawir, A. (2005). Analisis Kinerja Keuangan dan Perencanaan Keuangan Perusahaan. Jakarta: PT Gramedia Pustaka Utama.Setianan, A. R. & Adwitya, A. R. (2011). Analisis Pengaruh Pertumbuhan Aset dan EVA Terhadap Return Saham. Jurnal Bisnis dan Ekonomi, 2, (1), 54-67.Setiawan, H. & Sutapa. (2006). Analisis Faktor Penentu Struktur Modal (Studi Empiris pada Emiten Syariah di Bursa Efek Jakarta 2001-2004). Jurnal Akuntansi dan Keuangan, 5, (2), 203-215.Sharif, I., Ali A., & Jan, F. A. (2015). Effect of Dividend Policy On Stock Prices. Journal of Management Info, 6, (1), 55-85.Suliyanto. (2011). Ekonometrika Terapan: Teori dan Aplikasi Dengan SPSS Edisi Pertama. Yogyakarta: CV Andi Offset.Sugiyono. (2012). Metode Penelitian Bisnis. Bandung: Alfabeta.Sugiyono. (2016). Metode Penelitian Manajemen. Bandung: Alfabeta.Sugiyono. (2017). Metode Penelitian Bisnis. Bandung: Alfabeta.Sujarweni, V. W. (2015). Metodologi Penelitian Bisnis dan Ekonomi. Yogyakarta: Pustakabarupress.Sulindawati, N. L. G. E., Yuniarta, G. A., & Purnamawati, I. G. A. (2017). Manajemen Keuangan. Depok: PT Rajagrafindo Persada.Sumarni, I., Yusniar, M. W., & Jusniar, A. (2014). Pengaruh Investment Opportunity Set Terhadap Kebijakan Dividen. Jurnal Wawasan Manajemen, 2, (2), 201-211.Supranto. (2001). Statistik Teori dan Aplikasi Edisi Keenam. Jakarta: ErlanggaSutriani, A. (2014). Pengaruh Profitabilitas, Leverage, dan Likuiditas Terhadap Return Saham Dengan Nilai Tukar Sebagai Variabel Moderasi Pada Saham LQ-45. Journal of Business and Banking, 4, (1), 67-80.Sutrisno. (2009). Manajemen Keuangan Teori, Konsep, dan Aplikasi Edisi Pertama. Yogyakarta: Ekonisia.Tandelilin, E. (2010). Portofolio dan Investasi Teori dan Aplikasi Edisi Pertama. Yogyakarta: Kanisius.Widarjono, Agus. (2010). Analisis Statistika Multivariat Terapan Edisi Pertama. Yogyakarta.